40-fs hydrogen Raman laser. (December 2015) - Didenko, N.V.; Konyashchenko, A.V.; Kostryukov, P.V.; Losev, L.L.; Pazyuk, V.S.; Tenyakov, S.Yu.; Molchanov, V.Ya.; Chizhikov, S.I.; Yushkov, K.B.
Abstract: first Stokes pulses at a wavelength of were generated in a hydrogen SRS-converter pumped by orthogonally polarised double chirped pulses of a Ti : sapphire laser. To obtain a Stokes pulse close to a transform-limited one, a programmed acousto-optic dispersive delay line was placed between the master oscillator and regenerative amplifier. The energy efficiency of Stokes radiation conversion reached 22 %.